Tax evasion in a Cournot oligopoly with endogenous entry - Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2016)
If an additional competitor reduces output per firm in a homogenous Cournot-oligopoly, market entry will be excessive. Taxes can correct the so-called business stealing externality. We investigate how evading a tax on operating profits affects the excessive entry prediction. Tax evasion raises the number of firms in market equilibrium and can alter their welfaremaximizing number. In consequence, evasion can aggravate or mitigate excessive entry. Which of these outcomes prevails is determined by the direct welfare consequences of tax evasion and the relationship between evasion and the tax base. We also determine conditions which imply that overall welfare declines with tax evasion.
Keywords: D43; H26; L13; 330; Endogenous Entry; Oligopoly; Tax Evasion; Welfare